Birth Pattern Seasonality in Ethiopia: Evidence from National Demographic and Health Survey Data from 2000 to 2019 - Bezawit Alemu Bezabih; Mulugeta Shegaze Shimbre; Tamirat Gezahegn Guyo; Mesfin Mamo Utaile; Manaye Yihune; Aynalem Yemane Leyew; Getahun Koira Kolbaye; Habtamu Esubalew Bezie (Women's Health Reports)
Background: The periodicity of births and the factors that influence them have not been thoroughly investigated in Ethiopia. Hence, this study aimed to assess birth seasonality patterns in Ethiopia using data collected from Demographic and Health Surveys over the past two decades (2000–2019). Methods: A descriptive cross-sectional study was employed to record Ethiopian birth seasonality in greater detail than has previously been accomplished. The Demographic and Health Survey birth data were used to systematically document, evaluate, and compare the birth seasonality in Ethiopia. Results: Nationally, there was an early peak in the year, followed by a gradual decline. Regarding regional variation, in Afar and Somalia, the birth patterns show high variation, and Tigray, Amhara, Addis Ababa, and South Nation Nationality and Peoples Region exhibit relatively low variation in birth patterns, respectively. Conclusions: The birth pattern is not uniform and varies seasonally and with different locations as well as maternal demographics. This finding could assist in the prediction of seasonal birth rates, guide contraception campaigns, distribute vaccinations strategically, and design a proactive measure against childhood diseases using mathematical modeling.